1996
DOI: 10.1159/000292026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender on Perinatal Outcome in Pregnancies Complicated by Diabetes

Abstract: The aim of this study was to determine whether there is a gender-related difference in the morbidity and mortality of infants of diabetic mothers. We also wanted to identify risk factors associated with adverse pregnancy outcome, and create a perinatal morbidity index. We performed a retrospective review of 107 women whose pregnancies were singleton and complicated by diabetes. The subjects were divided according to the gender of the infant. The morbidity, mortality and confounding variables between the two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 10 publications
1
25
3
Order By: Relevance
“…Male fetal and newborn sex is an independent predictor of poor outcome in pregnancies affected by maternal diabetes [81]. One study showed newborn boys to have a higher risk for developing hypoglycemia and to need on average 2 days longer stays when admitted to the neonatal intensive care unit [81].…”
Section: Infants Born At Full Termmentioning
confidence: 99%
See 1 more Smart Citation
“…Male fetal and newborn sex is an independent predictor of poor outcome in pregnancies affected by maternal diabetes [81]. One study showed newborn boys to have a higher risk for developing hypoglycemia and to need on average 2 days longer stays when admitted to the neonatal intensive care unit [81].…”
Section: Infants Born At Full Termmentioning
confidence: 99%
“…One study showed newborn boys to have a higher risk for developing hypoglycemia and to need on average 2 days longer stays when admitted to the neonatal intensive care unit [81]. The investigators speculated that an explanation for the neonatal hypoglycemia could be related to the increased levels of human chorionic gonadotropine levels in diabetic mothers.…”
Section: Infants Born At Full Termmentioning
confidence: 99%
“…[3][4][5][6] It is well known that male sex is a risk factor for worse perinatal outcomes in the general obstetric population, 7 with increased risk of preterm delivery, 8 labor dystocia, 9 cord problems, 10 instrumental vaginal deliveries or cesarean section (CS), 10,11 macrosomia, 10 low Apgar scores, 10 major birth defects, 1 and perinatal mortality. 2,8,12 In relation to diabetic pregnancy, fetal sex has been considered only occasionally.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Suboptimal prenatal care along with poor maternal glycemic control, vasculopathy, infection, and pregnancy-induced hypertension are factors associated with poor perinatal outcome. 1,6,7 Congenital malformations, [8][9][10] macrosomia, 3,11,12 respiratory distress syndrome (RDS), 13,14 hypoglycemia, 3,[15][16][17] hyperbilirubinemia 18 and hypocalcemia 19 are some of the conditions most frequently diagnosed in the offspring of diabetic women.…”
mentioning
confidence: 99%